2002
DOI: 10.1007/s00114-002-0351-x
|View full text |Cite
|
Sign up to set email alerts
|

On the communicative significance of whistles in wild killer whales ( Orcinus orca )

Abstract: Killer whales (Orcinus orca) use pulsed calls and whistles in underwater communication. Unlike pulsed calls, whistles have received little study and thus their function is poorly known. In this study, whistle activities of groups of individually known killer whales were compared quantitatively across behavioural categories. Acoustic recordings and simultaneous behavioural observations were made of northern resident killer whales off Vancouver Island in 1996 and 1997. Whistles were produced at greater rates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…Resident killer whales do not appear to produce any sound type exclusively in association with a particular behavioral category, but do alter the rates of sound-type production in different behavior states (Bain 1986;Morton et al 1986;Ford 1989;Thomsen et al 2002). Thomsen et al (2002) found that resident killer whales produced short-range whistles and variable calls most commonly in socializing contexts, while stereotyped calls predominated in foraging and travel contexts. In his study of behavior and sound production of pods A1, A4, and A5, Ford (1989) found significant increases in the production of the short-range whistles, variable calls, and the N3 call type during beachrubbing, socializing, and group-resting behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resident killer whales do not appear to produce any sound type exclusively in association with a particular behavioral category, but do alter the rates of sound-type production in different behavior states (Bain 1986;Morton et al 1986;Ford 1989;Thomsen et al 2002). Thomsen et al (2002) found that resident killer whales produced short-range whistles and variable calls most commonly in socializing contexts, while stereotyped calls predominated in foraging and travel contexts. In his study of behavior and sound production of pods A1, A4, and A5, Ford (1989) found significant increases in the production of the short-range whistles, variable calls, and the N3 call type during beachrubbing, socializing, and group-resting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is mixed whether the various signal types in the repertoire or resident killer whales reflect the activities or motivations of signalers, as is documented for many primate sounds (Dittus 1988;Hauser & Marler 1993). No whistle or call type correlates exclusively with any Miller, PJO: Diversity in sound pressure levels and active space of killer whale sounds … 5 particular activity, but relative production rates of different call types and whistles vary with broad behavior metrics of the entire group (Bain 1986;Morton et al 1986;Ford 1989;Thomsen et al 2002). If the various sound types in the killer whale repertoire primarily serve a contact function of signaling group membership, as proposed by Ford (1989Ford ( , 1991, one might expect little variation in the estimated active space of different sound types in the repertoire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which are thought to help maintain group cohesion, coordinate behaviors, and mediate 85 group recognition (Ford 1989(Ford , 1991Miller 2002;Thomsen et al 2002). Based on 86 spectrographic contour and signal repetitiveness, they can be classified as discrete, 87 aberrant, or variable (Ford 1989;Rehn et al 2007).…”
Section: You May Notmentioning
confidence: 99%
“…We then used Kappa statistic to 179 test for interobserver reliability (Siegel and Castellan 1988). To compare levels of whistle activity between different behavior contexts, and to 205 be able to compare our findings to whistle activity in resident killer whales, we followed 206 the protocol of Thomsen et al (2002). In a first step, we divided all selected sections into 207 discrete subsamples that were characterized by the same behavior context.…”
mentioning
confidence: 99%